Supercritical Fluid Extraction of β-Carotene from Crude Palm Oil Using CO2 in a Bubbler Extractor: Mass Transfer Study - Reza Davarnejad (Iranian Journal of Chemistry & Chemical Engineering, 2014)
In this study, the diffusivity and volumetric mass transfer coefficients for the extraction of β-carotene from crude palm oil using CO2 solvent in supercritical fluid were determined in the pressure range of 7.5-17.5 MPa and temperature range of 80-120 ºC. For this purpose, a statistical method was applied in order to minimize the number of experiments required. The volumetric mass transfer coefficient for the extraction of β-carotene was then correlated as a function of pressure, temperature and extraction time in order to study the effect of each of these variables on the coefficient. The experimental results showed that the maximum volumetric mass transfer coefficient was around 2.486 × 10-2 s-1 at pressure of 7.5 MPa, temperature of 100 ºC and extraction time of 1 hour. The minimum volumetric mass transfer coefficient was 0.046 × 10-2 s-1 at pressure of 17.5 MPa, temperature of 120 ºC and extraction time of 5 hours. The optimum volumetric mass transfer coefficient was statistically obtained around 6.700 × 10-3 s-1 at pressure of 17.7 MPa, temperature of 100.5 ºC and extraction time of 3.9 hours.